Flood-Irrigated Corn Silage Cost-Return Budget (Custom Harvested) - O'Brien, Daniel M.; Dumler, Troy J. (My University, 2000)
This publication projects a budget that reflects expected income and costs based on flood-irrigated corn silage production.
MF581_2000_10
Keywords: MF581; Economics; Crops; MF